COMPETENCE OF LOCAL SELF-GOVERNMENTS: DEBATABLE ISSUES - Y. Blagov (Правоприменение, 2018)
Subject. The article is devoted to the discussion issues of competence of local self-government.The purpose of this paper is to show that the federal government passes such laws in order to build a single “power vertical” from a rural settlement to a constituent entity of the Russian Federation and above, since from his point of view it is easier to carry out public administration.The methodology. The author uses a dialectical method, a method of analysis and synthesis, a formal legal method, a comparative legal method.Results, scope of application. The competence of local self-government bodies consists of two parts: compulsory competence and optional competence. The compulsory competence includes issues of local importance of municipalities and certain transferred state powers. The optional competence of local self-government bodies includes the rights of local self-government bodies to resolve issues not related to issues of local importance of municipalities and other issues not within the competence of local government bodies and not excluded from their competence by federal and regional legislatures. Certain transferred state powers should not prevail over the powers related to the solution of issues of local importance and determine the functional purpose of local self-government bodies as such. It can be assumed that by their nature they should be related to the immediate interests of the local population.The rights of local self-government bodies to resolve issues not related to issues of local importance of municipalities are neither issues of local significance nor transferred by separate state powers. The meaning of their consolidation in Federal Law No. 131-FZ is to transfer to the local self-government authorities of powers which the state authorities cannot perform, but without the transfer of the corresponding material resources and financial resources that local governments should seek independently. The author offers his own solutions of this problem.The author criticizes the institution of redistribution of powers, since this institution contradicts the Constitution of the Russian Federation and the European Charter of Local Self-Government and comes to the conclusion that the issues of local importance of different types of municipalities overlap, as well as duplicate part of the powers of state authorities of the subjects of the Russian FederationConclusion. The new attempt to build a single vertical of power, which has been repeatedly undertaken in the history of Russia, is doomed to failure with all the ensuing consequences, especially acute during the economic crisis.